The Multi-Therapeutic Role of MSCs in Diabetic Nephropathy - Wang, Yi; Shan, Su-Kang; Guo, Bei; Li, Fuxingzi; Zheng, Ming-Hui; Lei, Li-Min; Xu, Qiu-Shuang; Ullah, Muhammad Hasnain Ehsan; Xu, Feng; Lin, Xiao; Yuan, Ling-Qing (Frontiers in Endocrinology, 2021)
Diabetic nephropathy (DN) is one of the most common diabetes mellitus (DM) microvascular complications, which always ends with end-stage renal disease (ESRD). Up to now, as the treatment of DN in clinics is still complicated, ESRD has become the main cause of death in diabetic patients. Recently, mesenchymal stem cells (MSCs), as cells with multi-differentiation potential and paracrine function, have attracted considerable attention in cell therapy. Increasing studies concerning the mechanisms and therapeutic effect of MSCs in DN have emerged. This review summarizes several mechanisms of MSCs, especially MSC-exosomes in the treatment of DN including hyperglycaemia regulation, anti-inflammatory and immune regulation, anti-fibrosis, angiogenesis promotion, and renal function protection. We also emphasize the enhanced therapeutic role of pre-treated MSCs in the DN process. This review provides convincing evidence for MSC therapy to be considered as a promising strategy in diabetic kidney disease amelioration.